A Charming Personality - V. Naniek Risnawati; Anastasia Lipursari (International Forum of Researchers and Lecturers, 2025)
A healthy and charming personality is an important element in socializing in the family, society and organization. Efforts that need to be developed so that the personality is charming must function fully by recognizing the weaknesses and strengths that are owned such as being open to experience, self-confident, living existentially, having a sense of freedom, physical and spiritual needs are met, and being able to develop oneself. And having broad insight, skills, good personality and a charming appearance that can not only utilize its advantages optimally, but is willing to face the shortcomings that exist within itself.